Comparison of male conflict behavior in chimpanzees (Pan troglodytes) and bonobos (Pan paniscus), with specific regard to coalition and post‐conflict behavior. Issue 6 (June 2017) - Surbeck, Martin; Boesch, Christophe; Girard‐Buttoz, Cédric; Crockford, Catherine; Hohmann, Gottfried; Wittig, Roman M.
Abstract : Coalitions among males during within group conflicts have a strong influence on the competitive and social environment within social groups. To evaluate possible variation in the occurrence of such coalitions in our closest relatives, chimpanzees and bonobos, we compared male aggression and coalitionary behavior in two natural communities, one of each species, with a similar size and composition. Furthermore we compared affiliative behavior that might be related to coalition formation among males. We found higher frequencies of aggression and a greater likelihood to form coalitions during within‐group conflicts among wild male chimpanzees at Taï compared to wild male bonobos at LuiKotale. The species differed in the predominant sex of the male coalition partners, with male bonobos forming coalitions more often with females, while male chimpanzees formed coalitions more often with other males. Compared to male bonobos, male chimpanzees showed higher rates of grooming and tended to reconcile more conflicts with other males. Overall our results showed lower frequencies of reconciliation among bonobos than those described in captivity and at artificial feeding sites. These findings add to the evidence that male cooperation and conflict resolution are potentially very different in bonobos and chimpanzees, despite the fact that these two species are closely related, live in multi‐male, multi‐female communities with a high degree of fission‐fusion dynamics and have female‐biased migration patterns. Given the correlation between aggressive, cooperative and some affiliative patterns within the species in our study, we hypothesize that the fitness benefits of male relationships are greater in chimpanzees compared to bonobos.